The intensification and reorientation of Sunni jihad ideology in the Crusader period : Ibn 'Asakir of Damascus and his age, with an edition and translation of Ibn 'Asakir's The Forty hadiths for inciting jihad - Mourad, Suleiman Ali. (Islamic History and Civilization, 2013)
The Intensification and Reorientation of Sunni Jihad Ideology in the Crusader Period examines the important role of Ibn ʿAsākir, including his Forty Hadiths for Inciting Jihad , in the promotion of a renewed jihad ideology in twelfth-century Damascus as part of sultan Nūr al-Dīn's agenda to revivify Sunnism and fight, under the banner of jihad, Crusader and Muslim opponents. This jihad vision was exclusively centered on selected quranic verses and prophetic hadiths. Ibn ʿAsākir and other Sunni scholars in twelfth- and thirteenth-century Syria departed from the earlier scholarly focus on legal nuances and aversion to invoke jihad in intra-Muslim conflicts. They championed this intensification and reorientation of jihad ideology in mainstream Sunni scholarship, and gave it a lasting legacy.